Infraestructura necesaria para el intercambio de germoplasma de yuca - Cock, James H. (International Center for Tropical Agriculture, 1983)
Adequate resources and infrastructure for the exchange of cassava germplasm are discussed according to the type of material received (sexual seed, cuttings, and meristems). The final objective of exchanging cassava germplasm among different countries is to obtain improved var.; in order to do so, the continuity of breeding programs that handle introduced genetic material should be assured along with professionals trained to manage the different ways of germplasm exchange, technical assistants, physical facilities such as tissue culture lab., greenhouses, and exptl. fields, and a mechanism for multiplying new var. and releasing them to farmers. (CIAT)